"Cured" but not "healed": The application of principles of palliative care to cancer survivorship. (April 2021) - MacDonald, Chelsea; Theurer, Julie A.; Doyle, Philip C.
Abstract: Application of principles of palliative care to the concept of survivorship may serve to establish an interdisciplinary approach to guide those treated for cancer through the experience of being "cured" but not "healed". Valuable lessons may be garnered from palliative care if its principles are considered within the context of survivorship. This work aims to define key terms including cured, healed, survivorship, and quality of life (QoL) and delineate the central tenets of palliative care and disease-modifying care. Since pursuit of a cure tends to dominate provision of oncological care, Western society's prevailing death denying attitudes often equate to the prioritization of advanced medial treatment to postpone death. Accordingly, the "modern paradox" of medicine (Cassell, 2004) is examined in consideration of the suffering that often results from advanced medical treatment that is intended to alleviate the cause of suffering and ultimately, "deny" death. However, owing to the profound consequences of advanced medical treatment and the associated losses of function concomitant with cancer, there is an apparent need for a framework of care that attends to these survivorship issues. When the experience of being cured but not healed is articulated through a theoretical discussion of liminality and the "remission society" (Frank, 1995), the applicability of palliative care to survivorship care becomes apparent. By embracing principles of palliative care, survivorship care may be guided by a theoretical foundation that provides cancer survivors with care that supports increased QoL, biopsychosocial symptom management, and a holistic perspective of the illness experience. Accordingly, application of palliative care to survivorship may establish congruence between notions of cured and healed. Highlights: Consideration of quality of life is often limited to palliative care. Quality of life is diminished even after cancer has been successfully treated. Palliative care principles should not be limited to those who are imminently dying. Palliative care may be applied to survivorship care to bolster quality of life.